2016
DOI: 10.1002/cbm.2001
|View full text |Cite
|
Sign up to set email alerts
|

Family intervention in a prison environment: A systematic literature review

Abstract: Consistency in findings across the wide-ranging studies suggested that family therapies may indeed be helpful for prisoners and their families, so further research is warranted. The fact that a randomised controlled trial proved feasible should encourage researchers to seek more robust data and to determine which form of intervention is effective and in which circumstances. It would also be useful to develop an improved understanding of mechanisms of change. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Family therapy services in this setting would ameliorate reintegration into the family's structure (Datchi, Barretti, & Thompson, 2016). A systematic literature review showed that all studies analyzed were able to show benefits of family interventions within this population (Roberts et al, 2017). Despite these results, there have not been substantial changes in family services availability or accessibility in these facilities (Roberts et al, 2017).…”
Section: Life While Incarceratedmentioning
confidence: 99%
“…Family therapy services in this setting would ameliorate reintegration into the family's structure (Datchi, Barretti, & Thompson, 2016). A systematic literature review showed that all studies analyzed were able to show benefits of family interventions within this population (Roberts et al, 2017). Despite these results, there have not been substantial changes in family services availability or accessibility in these facilities (Roberts et al, 2017).…”
Section: Life While Incarceratedmentioning
confidence: 99%
“…There are few published process evaluations of parenting programmes in prisons (Miller et al., 2014 ), and none that the author is aware of in relation to interventions for young incarcerated fathers. A review of family interventions more broadly in the prison environment concluded that there were problems delivering such interventions in this setting because of: limited engagement with families, high participant drop-out rates, prisoner concerns about confidentiality, practical barriers such as lack of suitable rooms, and low trust between prisoners and staff (Roberts et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therapy services have vast potential to provide psycho-education, improve relationships, and treat issues related to being incarcerated (Tadros & Finney, 2018). A systematic literature review indicated that all studies investigated were able to demonstrate the benefits of family interventions when used with the incarcerated population (Roberts et al, 2017). However, this lack of available services hinders the ability for siblings to remain in contact or address the issues brought on and maintained by incarceration despite the research showing incarcerated therapy's efficacy.…”
Section: Discussionmentioning
confidence: 99%